2021
DOI: 10.3390/ruminants1020011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Low-Moisture, Molasses-Based Block Containing Organic Sources of Trace Minerals and a Saccharomyces cerevisiae Fermentation Culture during the Feedlot Receiving Phase on Growth Performance, Efficiency of Dietary Net Energy Utilization, and Liver Trace Mineral Status in Newly Weaned Steer Calves

Abstract: The objective of this study was to evaluate the growth performance responses and liver trace mineral status of newly weaned steer calves offered a low-moisture, molasses-based block “stress tub” containing organic sources of trace minerals and a Saccharomyces cerevisiae fermentation culture during the first 21-d of a 42-d feedlot receiving phase. Newly weaned, single source Charolais x Angus steer calves (n = 46; body weight [BW] = 240; SEM = 1.0 kg) were used in a 42-d randomized complete block design feedlot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 18 publications
2
9
1
Order By: Relevance
“…In addition, on day 9 steers reached DMI equivalent to 2% of BW, which is the desired DMI for receiving calves ( Pritchard, 2005 ), and this likely contributed to the reduction in voluntary intake of the stress tub. A similar response was observed by Hamilton et al (2021) where steers reduced the consumption of the stress tub on day 5.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…In addition, on day 9 steers reached DMI equivalent to 2% of BW, which is the desired DMI for receiving calves ( Pritchard, 2005 ), and this likely contributed to the reduction in voluntary intake of the stress tub. A similar response was observed by Hamilton et al (2021) where steers reduced the consumption of the stress tub on day 5.…”
Section: Resultssupporting
confidence: 80%
“…Final BW and ADG tended ( P ≤ 0.10) to be greater for FORCE compared to TUB and CON by 5.4% and 9.4%, respectively, G:F did not differ by treatment ( P = 0.28). In the study conducted by Hamilton et al (2021) , steers were supplemented with the same stress tub used on this trial (Purina Animal Nutrition, St. Louis, MO, USA) during the first 21 day of a 42-day feedlot receiving phase and reported a tendency for 18.5% improvement on ADG for steers that received the stress tub supplementation. However, there were no significant differences observed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of both studies indicated that there was an adaptation period for animals to lick LB, and the LB intake was related to the quality of the basal diet. In addition, the cleanliness of the LB surface also affects intake [87]. The variation in LB intake is large, ranging from 12.3 g/d to 500.0 g/d (Table 3), and depends on body size, physiological condition, production stage and nutrient requirements of the animals.…”
Section: Factors Influencing Lick Block Intakementioning
confidence: 99%